Documentation of the volume of historical buildings through point clouds: an experiment at Pelourinho in Salvador, Bahia (Research, Society and Development, 2020)
In this work, a process flow was proposed for the construction of geometric models of a set of buildings located in Pelourinho, Salvador in Bahia. The workflow for the construction of textured models in SketchUP required the acquisition of aerial and terrestrial images of the buildings, the generation of point clouds and orthophotos by photogrammetric processes in Photoscan, the orthophoto treatment in Photoshop, and finally the production of point cloud sections in AutoCAD. The steps defined for the construction of geometric models made it possible to reach the goal. However, new methodologies need to be developed and refined to simplify processes, reducing labor and processing time.